Right hemihepatectomy combined with ligation of the common hepatic artery and gastroduodenal artery for the treatment of intrahepatic HHT: A case report - Xiang, Jifeng; Xie, Wei; Zhang, Cuncheng; Wang, Huaizhi (Frontiers in Surgery, 2022)
Hereditary haemorrhagic telangiectasia (HHT) is a rare disease that lacks effective treatment. Here, the authors report the case of a 30-year-old woman presenting with abdominal pain accompanied by severe malnutrition. After a definite diagnosis of HHT involvement in the liver, liver transplantation was the first-choice treatment according to the guidelines of HHT. However, the patient firmly refused liver transplantation. Finally, a new type of surgery, right hemihepatectomy combined with ligation of the common hepatic artery and gastroduodenal artery, was performed based on careful study of the case and with the maximum benefit of the patient in mind. Although the patient developed transient liver dysfunction after surgery, she eventually recovered well and continued to be followed up. As far as we know, this is the first report of this kind of surgery for the treatment of intrahepatic HHT.